Justice among Nations - Stephen C. Neff (Harvard University Press, 2014)
George Washington may not have chopped down a cherry tree, but recent evidence has uncovered a misdeed of a diff erent, and perhaps more serious, character: a failure to return two books borrowed from the New York Society Library in October 1789. Moreover, there is no record of a gallant confession of wrongdoing. By way of mitigation, it must be admitted that Washington was a busy man at the time, having recently been installed as the fi rst president of the United States. When the scandal was exposed (in 2010), the staff at Mount Vernon hastened to make amends by providing replacement volumes to the library. Th e aff air attracted some public attention by virtue of the accumulated fi ne for late return— estimated by some at $300,000. Less notice was taken of what the books were. One was a volume of British House of Commons debates. Th e other was a book called Th e Law of Nations, by a Swiss writer named Emmerich de Vattel. It is hard to say which of the two tomes was the livelier read. In the House of Commons debates, there would have been some of the oratorical fl air characteristic of that eloquent age. But there was fl air, too— of an intellectual kind— in Vattel’s treatise. His Law of Nations, written in 1757, had the distinction of being the fi rst book on international law to be written for a general audience— if not quite for the person in the street, then at least for persons concerned with statecraft generally. In marked contrast to anything that had gone before, Vattel’s book was a literary gem— written in a sparkling style, simple and elegant throughout. Vattel, a working diplomat himself, explicitly hoped that his exposition would prove useful to men of aff airs, dealing with real- world problems, and not merely to moral phi los o phers.With Washington as one of his readers, he could claim some deserved satisfaction on this point.